El Derecho de la Moda, sus principales movimientos y lo más trendy: el Fashion Tech - Fasson Llosa, Annalucia (2021)
Through this article, the author outlines the main movements of Fashion Law, which have been developed in order to meet the needs of consumers. It emphasizes trends, which cannot be delimited to the extent that they are the product of specific niches in the community.